Stock Market Development and Sustainable Economic Growth in Nepal: A Decade Experiences (Shiksha Shastra Saurabh, 2025)
Stock market is the mirror of economic growth of any country. It directly links with the economic growth and measures the sustainable economic growth. It has various causes like the political instability, low development national budget, high inflation, unstable economic policies and economic crisis, role of the Rastra Bank, World Bank decectatives, correction, institutional disparities and many others including political and economic scenario in which Nepal is facing from the early decades. This study mainly looks at how Nepal’s growth of stock market links to its long-term economic development and Nepal’s financial sector and stock market. This study uses data from (2014 to 2024) to see in wh t way Nepal’s capital market has formed the country’s economic growth. These changes show up in the way people invest, the rules shape on the market a d the bigger economic areas. This research delves into how stock market indicators show market capitalization, trading volume and price upsets line up with big-picture economic factors like GDP growth, inflation and gross capital formation. The study uses time-series econometric tools including Granger Causation tests to look at both short-term market ups and downs and longer-term links between the stock market and economic growth. There’s a modest but positive relationship between Nepal’s stock market and its economic development. Equally sides seem to i fluence each other over time but there are real obstacles. Through those changes, the stock market could play a much bigger role in helping the country to develop sustainable economic growth. This research adds information on frontier market and gives clear steps to governments, development agencies and investors.